Reducing Contact Stress of the Surface by Modifying Different Hardness of Femoral Head and Cup in Hip Prosthesis - Saputra, Eko; Budiwan Anwar, Iwan; Jamari, J.; Heide, Emile van der (Frontiers in Mechanical Engineering, 2021)
The wear of hip prosthesis due to applied load and sliding distance during the patient's daily activity cannot be avoided. Wear causes osteolysis or metallosis due to the wear debris produced by the wear process. Several methods were used to reduce wear in metal-on-metal hip prostheses. One of the efforts performed to reduce wear was the differential-hardness concept. Based on the literature, the fine surface roughness of the femoral head are the reason why the hip prosthesis with differential-hardness reduces wear. Besides, the differential-hardness will contribute to the difference of modulus elasticity then influenced the contact stress on the surface contact. According to Archard's wear law, wear on the material pair is affected by contact stress. Therefore, the analysis of contact stress on the hip prosthesis with differential-hardness is important to investigate. The investigation performed by the static contact of two-dimensional axisymmetric with frictionless by using finite element simulation. The simulated models are the alumina on alumina, alumina on SS316L, CoCr vs CoCr, CoCr vs SS316L, and SS316L vs UHMWPE. The purpose of this study is to determine the contact stress on the surface contact due to differential-hardness of the femoral head and cup. The results of simulations show that the differential-hardness marked by differences in the modulus of elasticity can reduce the contact stress on the surface contact if compare with the similar hardness.